Do patients think cannabis causes schizophrenia? - A qualitative study on the causal beliefs of cannabis using patients with schizophrenia - Buadze, Anna (BioMed Central, 2010)
BACKGROUND: There has been a considerable amount of debate among the research community whether cannabis use may cause schizophrenia and whether cannabis use of patients with schizophrenia is associated with earlier and more frequent relapses. Considering that studies exploring patients' view on controversial topics have contributed to our understanding of important clinical issues, it is surprising how little these views have been explored to add to our understanding of the link between cannabis and psychosis. The present study was designed to elucidate whether patients with schizophrenia who use cannabis believe that its use has caused their schizophrenia and to explore these patients other beliefs and perceptions about the effects of the drug. METHODS: We recruited ten consecutive patients fulfilling criteria for paranoid schizophrenia and for a harmful use of/dependence from cannabis (ICD-10 F20.0 + F12.1 or F12.2) from the in- and outpatient clinic of the Psychiatric University Hospital Zurich. They were interviewed using qualitative methodology. Furthermore, information on amount, frequency, and effects of use was obtained. A grounded theory approach to data analysis was taken to evaluate findings. RESULTS: None of the patients described a causal link between the use of cannabis and their schizophrenia. Disease models included upbringing under difficult circumstances (5) or use of substances other than cannabis (e. g. hallucinogens, 3). Two patients gave other reasons. Four patients considered cannabis a therapeutic aid and reported that positive effects (reduction of anxiety and tension) prevailed over its possible disadvantages (exacerbation of positive symptoms). CONCLUSIONS: Patients with schizophrenia did not establish a causal link between schizophrenia and the use of cannabis. We suggest that clinicians consider our findings in their work with patients suffering from these co-occurring disorders. Withholding treatment or excluding patients from certain treatment settings like day-care facilities or in patient care because of their use of cannabis, may cause additional harm to this already heavily burdened patient group.